2008
DOI: 10.1063/1.2945165
|View full text |Cite
|
Sign up to set email alerts
|

Construction of the free energy landscape of biomolecules via dihedral angle principal component analysis

Abstract: A systematic approach to construct a low-dimensional free energy landscape from a classical molecular dynamics (MD) simulation is presented. The approach is based on the recently proposed dihedral angle principal component analysis (dPCA), which avoids artifacts due to the mixing of internal and overall motions in Cartesian coordinates and circumvents problems associated with the circularity of angular variables. Requiring that the energy landscape reproduces the correct number, energy, and location of the sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
254
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 201 publications
(263 citation statements)
references
References 53 publications
5
254
0
4
Order By: Relevance
“…By considering these two aspects, we only include dihedral angles in the restraint potential. Very recently, Stock and coworkers 29 showed that full-dimensional free energy landscape could be reproduced accurately by dihedral-angle principal component analysis. In our work, we only restrain two dihedral angles: phi and psi, for the backbone of the peptide and the nonhydrogen atom dihedral angles for side chains.…”
Section: Free Energy Calculation Algorithmmentioning
confidence: 98%
“…By considering these two aspects, we only include dihedral angles in the restraint potential. Very recently, Stock and coworkers 29 showed that full-dimensional free energy landscape could be reproduced accurately by dihedral-angle principal component analysis. In our work, we only restrain two dihedral angles: phi and psi, for the backbone of the peptide and the nonhydrogen atom dihedral angles for side chains.…”
Section: Free Energy Calculation Algorithmmentioning
confidence: 98%
“…The characterization of the free energy landscape of larger systems is less straightforward and therefore needs to be carried out in a systematic manner. With this end in mind, in the following we consider the free energy landscape of hepta -alanine (Ala 7 ), which was obtained from an 800 -ns MD simulation in aqueous solution at 300 K [5] . To get a fi rst impression, Figure 2.3 shows two -dimensional representations of the free energy landscape of Ala 7 , as obtained from an dPCA of the backbone dihedral angles.…”
Section: Dimensionality Of the Free Energy Landscapementioning
confidence: 99%
“…Doing so, we found that k = 23 are a suitable number of clusters (see Ref. [5] for details). This fi ndings are reconfi rmed by the results of a kinetic clustering of the Ala 7 trajectory, that is, a clustering that defi nes its states through their metastability rather than through geometric similarity.…”
Section: Characterization Of the Free Energy Landscape: States Barrimentioning
confidence: 99%
See 1 more Smart Citation
“…Although most problems in the protein structure field depend on coordinate-based methods, backbone-angle-based methods have provided an attractive alternative approach in various protein structure-related problems, such as protein structure prediction (Simons et al, 1999;Hamelryck et al, 2006;Boomsma et al, 2008;Zhao et al, 2010), protein loop modeling (Ting et al, 2010), model quality assessment (Benkert et al, 2008;Gao et al, 2009;Archie and Karplus, 2009), prediction server ranking (Qiu et al, 2008;Maadooliat et al, 2013a), protein structure alignment (Miao et al, 2008;Challis and Schmidler, 2012), free energy function learning (Mu et al, 2005;Altis et al, 2008;Riccardi et al, 2009), and molecular dynamics simulation (Altis et al, 2007). In this paper, we focus on statistical modeling of the bivariate distribution of protein backbone angles.…”
Section: Introductionmentioning
confidence: 99%